Answer:
x = -3, ![$ \frac{3}{2} $](https://tex.z-dn.net/?f=%24%20%5Cfrac%7B3%7D%7B2%7D%20%24)
Step-by-step explanation:
The given quadratic equation is: ![$ 2x^2 = 9 - 3x $](https://tex.z-dn.net/?f=%24%202x%5E2%20%3D%209%20-%203x%20%24)
This can be written as: ![$ 2x^2 + 3x - 9 = 0 $](https://tex.z-dn.net/?f=%24%202x%5E2%20%2B%203x%20-%209%20%3D%200%20%24)
To solve a quadratic equation of the form
we use the formula:
![$ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} $](https://tex.z-dn.net/?f=%24%20x%20%3D%20%5Cfrac%7B-b%20%5Cpm%20%5Csqrt%7Bb%5E2%20-%204ac%7D%7D%7B2a%7D%20%24)
Here, a = 2; b = 3; c = - 9
Therefore, the roots of the equation are:
![$ x = \frac{- 3 \pm \sqrt{9 - 4(2)(-9)}}{2(2)} $](https://tex.z-dn.net/?f=%24%20x%20%3D%20%5Cfrac%7B-%203%20%5Cpm%20%5Csqrt%7B9%20-%204%282%29%28-9%29%7D%7D%7B2%282%29%7D%20%24)
![$ \implies x = \frac{-3 \pm \sqrt{81}}{4} $](https://tex.z-dn.net/?f=%24%20%5Cimplies%20x%20%3D%20%5Cfrac%7B-3%20%5Cpm%20%5Csqrt%7B81%7D%7D%7B4%7D%20%24)
![$ \implies x = \frac{-3 \pm 9}{4} $](https://tex.z-dn.net/?f=%24%20%5Cimplies%20x%20%3D%20%5Cfrac%7B-3%20%5Cpm%209%7D%7B4%7D%20%24)
We get two values of 'x', viz.,
x =
and ![$ \frac{- 3 - 9}{4} $](https://tex.z-dn.net/?f=%24%20%5Cfrac%7B-%203%20-%209%7D%7B4%7D%20%24)
![$ \implies x = \frac{6}{4} \hspace{5mm} \& \hspace{5mm} \frac{-12}{4} $](https://tex.z-dn.net/?f=%24%20%5Cimplies%20x%20%3D%20%5Cfrac%7B6%7D%7B4%7D%20%5Chspace%7B5mm%7D%20%5C%26%20%5Chspace%7B5mm%7D%20%5Cfrac%7B-12%7D%7B4%7D%20%24)
⇒ x = -3, 3/2
Since the factors of the quadratic equation is asked, we write it as:
(x + 3)(x -
) = 0
because, if (x - a)(x - b) are the factors of a quadratic equation, then 'a' and 'b' are its roots.
Multiply (x + 3) and (x -
to see that this indeed is the given quadratic equation.